GIM-Sim:1 and 2: addressing the need for curriculum-linked simulation for internal medical trainees - Kieran Hardern; Hannah Parker (Future Healthcare Journal)
Introduction: An overhaul of medical training introduced internal medical training (IMT) Stage 1 in 2019, refocusing early training on managing diverse medical conditions alongside professional attitudes. The new curriculum mandated ‘simulation teaching involving human factors’, yet no national courses, guidelines or funding exist to support delivery.1In our experience, course development relies on local departments and the motivation of resident doctors. While many rotational trainees with a passion for education establish local courses, these often falter when developers rotate. NHS England acknowledges the challenge of training all medical professionals without expanding educator capacity to meet workforce needs.2Recognising this gap, we sought to develop realistic simulation courses addressing common medical emergencies, integrating human factors essential to everyday clinical interactions. Our model ensures sustainability by having participants return as faculty for future courses. Methods: A course series was developed called ‘GIM Sim’, beginning with two simulation days for IMT1s and IMT2s. Both days were mapped to the IM curriculum, covering key generic and clinical competencies while reflecting ‘real-life’ practice (Table 1).Additional benefits included using current registrars as faculty and incorporating a troubleshooting session, providing a safe space to discuss any questions. All candidates completed a pre-course questionnaire to identify concerns about their role. Scenarios were then pre-allocated based on responses, allowing faculty to address individual learning needs alongside broader curriculum goals. Results and discussion: Since 2022, 39 doctors have attended the course series (20 at IMT1 and 19 at IMT2).All attendees (100%) found the sessions interesting and relevant to their role, and all would recommend the course to colleagues. Confidence ratings were assessed pre- and post-course, with both courses showing an increase (Table 2).Written feedback praised the ‘approachable team and relaxed learning environment’, while scenarios were described as ‘challenging but realistic, with helpful directed feedback’. Six former participants, now IMT3 or higher, have become recurring faculty, ensuring the programme remains an integral part of IMT Stage 1 within the Trust. Conclusion: Sustaining simulation courses is challenging for a non-consultant medical team alongside full-time clinical duties. Research posts offer in-programme training for clinicians in the form of Academic Clinical Fellowships; however, no such pathway exists for passionate clinical educators.Our next goal is to expand our faculty and introduce these courses at additional centres, using the same model of inducting former participants to lead future iterations, allowing us to develop the course series without existing days faltering. Later in 2025, we will extend these courses to a larger neighbouring Trust and launch a similarly sustainable programme for the IM Stage 2 curriculum, integrating human factors.